A arte de liderar com sentido: uma experiência inaciana no Colégio Anchieta de Nova Friburgo / RJ - Ferreira, Juliana Silva (Universidade do Vale do Rio dos Sinos, 2025)
This article investigates the integration of Ignatian Pedagogy in the development of educational leadership, using Colégio Anchieta, located in Nova Friburgo/RJ, as a case study. Grounded in the spiritual and pedagogical foundations of the Ignatian tradition, the study seeks to understand how this approach can be applied to institutional management, promoting a leadership model that combines efficiency, ethics, and commitment to the educational mission of the Society of Jesus. The analysis focuses on the Programa Docente Magis (PDM), originally designed for continuous teacher development, but which demonstrates significant potential to be adapted for training school leaders and administrators. Anchored in the Jesuit leadership pillars—self-awareness, ingenuity, love, and heroism—and the values of Ignatian Pedagogy, the program emphasizes integral formation, discernment, active listening, and shared responsibility as key elements for enhancing organizational culture and aligning leadership practices with institutional values. Using a mixed-methods approach, including both quantitative and qualitative data, the research examines perceptions of institutional leadership through the lens of Ignatian spirituality. The findings suggest that expanding the PDM to include leaders and administrators can strengthen institutional identity, a sense of mission, and the practice of cura personalis, fostering a culture of care, excellence, and service. The study concludes that leadership development rooted in the Ignatian tradition is essential for a transformative educational management model—one that builds human connections, inspires meaningful change, and contributes to the common good, reaffirming the strategic role of leadership in fulfilling the Jesuit educational mission.
Keywords: Pedagogia Inaciana; Liderança educacional; Formação continuada; Espiritualidade; Formação integral; Ignatian Pedagogy; Continuing education; Spirituality; Holistic Education